Insuring adequate spacing between underground distribution conductors in conduit and gas lines. - Parker, T.J (IEEE Transactions on power delivery)
The effects of faults occurring on secondary cables in plastic conduit energized at 240 V were evaluated under simulated field conditions. Secondary cables were intentionally faulted inside polyvinyl chloride (PVC) and polyethylene (PE) conduit. The test setup represented a typical, residential single-phase circuit consisting of a padmount transformer with a length of secondary cable. The fault characteristics (voltage and current waveforms) and temperatures on the exterior of the conduit near the fault were recorded. The condition of the conduit after the fault was also assessed.